Archaeology and the Moving Image. (November 2014) - Morgan, Colleen
<x content-type="archive" xml:space="preserve">Abstract</x> Archaeological filmmaking is a relatively under-examined subject in academic literature. As the technology for creating, editing, and distributing video becomes increasingly available, it is important to understand the broader context of archaeological filmmaking; from television documentaries to footage shot as an additional method of recording to the informal 'home videos' in archaeology. The history of filmmaking in archaeology follows innovations within archaeological practice as well as the availability and affordability of technology. While there have been extensive analyses of movies and television shows about archaeological subjects, the topic of archaeological film has been characterized by reactions to these outside perspectives, rather than examinations of footage created by archaeologists. This can be understood to fall within several filmic genres, including expository, direct testimonial, impressionistic, and phenomenological films, each with their own purpose and expressive qualities. Footage taken on site can also be perceived as a form of surveillance, and can modify behaviour as a form of panopticon. Consequently, there are considerations regarding audience, distribution, and methods for evaluation, as these films are increasingly available on social media platforms. This paper explores the broad context for archaeological filmmaking and considers potential futures for the moving image in archaeology.